PERAN KEPEMIMPINAN VISIONER KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI SMP NEGERI 7 PEMALANG - Herlinda; Widya Nurhayati; Teguh Gunarso; Ngurah Ayu Nyoman M (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study analyzes the role of visionary leadership by school principals in enhancing the quality of education at SMP Negeri 7 Pemalang. A qualitative approach was employed with data collected through observations, interviews, and documentation. Data analysis was conducted interactively through data reduction, data display, and drawing conclusions. The results indicate that the principal effectively plans strategies, controls educational quality, and develops the performance of teachers and students collaboratively. These strategies have had a positive impact on the quality of educational inputs, processes, and outputs. It is recommended that this leadership model be adopted by other schools to achieve excellent and competitive education.